Level Kognitif Siswa dalam Menyelesaikan Soal Program Linear Ditinjau dari Jenis Kepribadian - Melinda, Anastasia; Syarifah Fadillah; Muchtadi (Indo-MathEdu Intellectuals Journal, 2023)
The aim of this research is to determine the cognitive level of class XI IPS 1 student at SMA Negeri 1 Seberuang in solving linear programming problems in terms of personality type. This type of research is qualitative descriptive research. The form of research used is case study research. The subjects of this research were 27 students. Subjects are categorized based on each student's cognitive level. This research began by providing a personality type questionnaire, cognitive level tests, and interviews to categorize students' ability levels. After that, proceed with analyzing and categorizing based on personality type and cognitive level to determine the research subjects who will be interviewed by selecting 6 subjects consisting of 3 students with extroverted personalities whose cognitive levels are high, medium, and low and 3 students with introverted personalities whose cognitive levels are high, medium. and low. From the research results, it was concluded that students with introverted personalities had a higher cognitive level than students with extroverted personalities.